Macroeconomic Factors on Islamic Stock Returns - Muslimin, Aditia Pranugroho; Retnaningdiah, Dian (Universitas Negeri Yogyakarta, 2025)
The development of Islamic economics gave birth to the Islamic capital market as an alternative investment based on sharia principles, such as the prohibition of usury and speculation, with supervision from the National Sharia Council of the Indonesian Ulema Council (DSN-MUI). In Indonesia, the transformation of the Islamic capital market began with the launch of the Islamic Mutual Fund by PT Danareksa Investment Management (1997) and the Jakarta Islamic Index (JII) by the Indonesia Stock Exchange (2000), which laid the foundation for the significant growth of Islamic instruments. This study aims to analyze the effect of macroeconomic factors, namely inflation, interest rates, exchange rates, Gross Domestic Product (GDP), and foreign exchange reserves on stock returns in companies listed on the Jakarta Islamic Index (JII) during the period 2014-2023. The method used is panel data regression analysis with a secondary data-based quantitative approach. The results showed that inflation has a positive and significant effect on stock returns, while interest rates have a negative and significant effect. On the other hand, exchange rates, GDP, and foreign exchange reserves do not have a significant effect on stock returns.